Capability poverty by deficits in net dietary intake at early age – neglected by the Rangarajan poverty line - Eklund, Per A (Indian Journal of Community Health, 2014)
Introduction: The Rangarajan Expert Group set up to improve the methodology for measuring poverty fails to: (i) shift from uncertain assessments of calorie - consumption poverty to use of ‘direct’ determinants of deficits in net dietary intake, indicating risk of capability poverty; [1,2] (ii) include vegetables and fruit as an additional food category; and (iii) consider inequity in child nutritional outcomes. The 2014 poverty line includes raised expenditure on calories, meat, protein and fats and four non-food categories. The report avoids the issue of disparities in social protection that drive capability poverty. It concludes that its normative food basket does offer “a basis for optimism on associated nutrition-status outcomes”. Rationale: Inferior nutrition status, compounded in the lowest wealth groups, argues for use of ‘direct’ indicators of net deficits in nutritional intake in poverty assessments, such as the growth curve of children and measurements of anaemia. [3,4] Objective: Where, and how, do diseases and poor nutrients, contribute to rising deficits in net dietary intake? In 20 of 106 districts, in six states, from the 2002-04 LDHS-2 to the 2011 Hungama survey, child underweight (<-2SD, 5y) increased by more than 5 percentage points. [5] Why? Methods and results: Literature confirms socio-economic rationale of addressing capability poverty indicated by child chronic undernutrition. [6,7,8] Iron-poor vegetarian diets, limited coverage of iron supplementation to young children and of food fortification in low-income settings, argue for raised intake of fruit and vegetables. [9] Conclusion: Capability poverty, driven by nutritional deficits at early age, perpetuates socio-economic disparities. Will location-specific determinants be addressed of rising deficits in net dietary intake at early age? Will iron - rich vegetables and fruits become an additional food group in a revised poverty line?